2005
DOI: 10.1007/s11090-005-4991-4
|View full text |Cite
|
Sign up to set email alerts
|

System for In Situ Characterization of Nanoparticles Synthesized in a Thermal Plasma Process

Abstract: We have designed a particle diagnostic system that is able to measure particle size and charge distributions from low stagnation pressure (≥746 Pa) and high temperature (2000-4000 K) (Si, Ti, Si-Ti-N, etc.) synthesized with our thermal plasma reactor. We found that the mean particle size increases with operating pressure and reactant flow rates. We also found that most particles from our reactor are neutral for particles smaller than 20 nm, and that the numbers of positively and negatively charged particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Calorimetric energy balance measurements determined temperatures in the range of a few thousand K and due to the immediate cooling process, a quench rate greater than 5 x 10 6 K s -1 was found. Sophisticated sampling techniques have been developed for near real time inline-measurements of particle size distribution and it is found that nanoparticles sizing between a few and hundred nm in diameter can be achieved depending on pressure and precursor concentration 47 . DC arc discharge enables for the production of a few grams per hour of spherical, nanosized silicon particles, while the steep temperature gradient prevents them from aggregation.…”
Section: Plasma Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Calorimetric energy balance measurements determined temperatures in the range of a few thousand K and due to the immediate cooling process, a quench rate greater than 5 x 10 6 K s -1 was found. Sophisticated sampling techniques have been developed for near real time inline-measurements of particle size distribution and it is found that nanoparticles sizing between a few and hundred nm in diameter can be achieved depending on pressure and precursor concentration 47 . DC arc discharge enables for the production of a few grams per hour of spherical, nanosized silicon particles, while the steep temperature gradient prevents them from aggregation.…”
Section: Plasma Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…To study nano-particle size distribution, as produced under plasma conditions, a variety of approaches have been used for performing such measurements, including laser light scattering (LLS) [8][9][10][11], particle mass spectrometry (PMS) [12][13][14][15][16], direct sampling (DS) [13,[17][18][19][20][21] and the use of a plasma as a detection source [22,23]. The LLS method has considerable appeal in this application because it is both non-intrusive and it provides information on the plasma flame without intervention in the chemical and physical processes present.…”
Section: Introductionmentioning
confidence: 99%
“…A compelling need for the reduction or elimination of the disturbances provides the motivation to perfect the direct sampling methods. Rao et al [18] and Wang et al [19] have analyzed the aerosol samples on-line using a scanning electrical mobility spectrometer (SEMS), a device capable of high-resolution, near-time measurement of aerosol size distributions for particle sizes down to about 4 nm. In brief, this system utilizes an ejecto-dilutor system to sample particles from the hot vacuum zone through a water-cooled sampling probe and to adjust particle concentrations to a suitable level for measurements with SEMS.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques are used to carry out these analyses as summarized in the work of Hafiz et al [16] namely laser light scattering [17], sampling from the exhaust of turbomolecular pumps [18,19], mobility analysis at low pressure [20] and particle beam mass spectrometry [21]. These techniques all have limitations and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, PBMS (a system developed at the University of Minnesota) is restricted in the particle size range between 5 nm and 500 nm. Hafiz attempted to overcome the drawbacks by developing a sampling scheme combining an air ejector with a scanning mobility particle sizer [16]. This scheme operated in the range of 3-200 nm.…”
Section: Introductionmentioning
confidence: 99%